Somatization is associated with worse outcome in a chiropractic patient population with neck pain and low back pain. (February 2016) - Ailliet, L.; Rubinstein, S.M.; Knol, D.; van Tulder, M.W.; de Vet, H.C.W.
Abstract: Aim: To determine if psychosocial factors are associated with outcome in patients with neck pain or low back pain. Methods: In a prospective, multi-center chiropractic practice-based cohort study in Belgium and The Netherlands, 917 patients, of which 326 with neck pain and 591 with low back pain, completed self-administered questionnaires at baseline, following the second visit, and at 1, 3, 6 and 12 months. Psychosocial factors assessed at baseline were: distress, depression, anxiety and somatization via the Four Dimensional Symptom Questionnaire, patient's beliefs regarding the effect of physical activity and work on their complaint via the Fear Avoidance Beliefs Questionnaire, and social support via the Feij social support scale. Primary outcome measures were perceived recovery, pain intensity, and functional status which was measured with the Neck Disability Index and Oswestry Disability Index. A univariable regression analysis to estimate the relation between each psychological variable and outcome was followed by a multivariable multilevel regression analysis. Results: There were no differences in baseline patient characteristics between the patient population from Belgium and the Netherlands. Somatization scores are consistently associated with perceived recovery, functional status and pain for both neck pain and low-back pain. Depression was associated with poorer functioning in patients with LBP. There was a small association between fear and function and pain for patients with neck pain or low-back pain. Conclusion: Somatization was the only variable consistently found to be associated with diminished perceived recovery, higher degree of neck or low back disability, and increased neck or low back pain. Highlights: Chiropractic patients do not present with complicated psychological profiles. Outcome measures in this study are pain, functional status and perceived recovery. Somatization was associated with worse outcome in patients with neck pain. Somatization was also associated with worse outcome in patients with LBP. Depression is only associated with decreased functional status for patients with LBP.